A COMPARISON OF FINANCIAL ROBUSTNESS IN THE UNITED STATES AND TURKEY DURING 2007-2010 - Bennett, Paul; Erdogan, Oral (Emerald Group Publishing Ltd, 2011)
This study aims to explain that more conservative and supervised but supported banking system can be an advantage during the crises periods. We use the US banking system as the origin of the recent collapse, and the Turkish banking as the more profitable one during the recent crisis years. We have found evidence that, in the context of the specific type of externally initiated yet spreading crisis of confidence and funding that affected world institutions, the structure of the Turkish banks actually turned out to protect the Turkish financial system.
Keywords: Monetary Policy; Bank Capital; Financial Crisis; United States; Turkey